Experimental and simulation study of vibration effect on pipeline at UTHM Biodiesel Pilot Plant - Noor Hidayu Yusman Zulhadi; Rohani Rahmad (Progress in Engineering Application and Technology, 2022)
Vibration is an unavoidable reality in the design of pipe systems. The movement of the rotating equipment like compressor, pump, and fan can causes vibration on the pipeline system. The force from the rotating equipment produces the excitation force on the pipeline. This research is to study the vibration effect on the pipeline system at the centrifugal pump. In this study, the measurement of vibration on pipeline was carried out by using vibration analyzer. This experiment was conducted at UTHM Biodiesel Plant. Then, the simulation for analyzing the pipeline's vibration was carried out using the ANSYS Workbench software. The modal analysis and harmonic response on ANSYS were used to identify the pipeline natural frequency and frequency response. The speed of revolution per minute for the centrifugal pump motor is 2910 rpm and it used as the rotational velocity for modal analysis. The rotating force produced by the motor at the centrifugal pump was 27.07 Nm. The rotating force was used for the simulation on harmonic response analysis to obtain the critical peak of frequency response of displacement, velocity, and acceleration. This research is expected to obtain the maximum and minimum natural frequency, and also the maximum peak response of the pipeline. By investigating the impact of the rotating equipment on the pipeline, we were able to identify the maximum frequency for the pipeline based on the simulation and measure the vibration on the pipeline through the experiment.